Sistem Pengangkatan dan Hak Kewarisan Anak Angkat Menurut Adat Tionghoa di Kota Jambi - Maryati Maryati; Syarifa Mahila; Hisba Hisba; Triamy Rostarum; Musyaiyadah Musyaiyadah; Putri Aprilia Ernawati (Wajah Hukum, 2023)
This research is to find out and analyze the adopted child system according to Chinese customary provisions in Jambi. The approach used is the case approach, the concrete case approach that occurs in the field and the sociological approach, namely the legal approach carried out in practice as a determinant, to test the truth of science, using the scientific method. The purpose of adoption itself is to help others. Likewise regarding the right to inherit from adopted children there is no standard provision according to custom, but adoptive parents will give the rights of adopted children according to their abilities. The Chinese traditional adoption ceremony is carried out in a pagoda, and not through other official institutions. And the appointment was very simple, witnessed by the biological family and adoptive parents of two people from the family of the adoptive parents and biological parents. and given a small amount of money on the part of the child, permanent custody of the biological parents